The South African constitutional Court and the Rule of Law: The Masethla Judgment, A Cause for Concern - Krüger, Rósaan (Potchefstroom Electronic Law Journal, 2017)
The rule of law as a foundational constitutional value constrains the exercise of public power but the precise limits of the constraints it sets are not well defined. In Masethla v President of the Republic of South Africa,[1] the majority of the Constitutional Court opted for an interpretation of this value that frees the President from adherence to the demands of procedural fairness when exercising certain constitutional powers. This note will investigate the soundness of that interpretation against the background of theoretical expositions of the rule of law and earlier Constitutional Court judgments.